BULGARIAN LITERARY POETICS AND STYLISTICS IN THE PERIOD 1970 - 2020 - Evdokiya Borisova (Езиков свят)
This article is a fragment of a larger study, which is intended to be a chapter of a collective monograph with the working title “Bulgarian Literary Studies – History, Poetics, and Stylistics during the Past Half-Century”. The time span covers the decades fom 1970 to 2020, and the methodology of the ambitious review includes descriptive, but also theoretical-judgmental and critical discourse. Initially the target audience of the volume was the foreign reader, for whom the Bulgarian literary studies are outlined against the background of the large Slavic family of literary schools. However, our claims are that it would be interesting and useful to the Bulgarian reader as well. The article offers a brief overview of the development and state of Bulgarian literary and theoretical thought in the last five decades. It traces the schools, conceptual ideas, and traditions in the study of literature over the ambitious period of half a century, including biographical texts by literary theorists and specialists in literary poetics and stylistics. Specific analyses of Bulgarian and world literary classics are also provided, illustrating the directions and trends in the development of Bulgarian literary and academic thought. The main representatives of several generations of literary theorists, known not only in Bulgaria, but also in Europe and the world, have been selected. The tangible results are outlined, as well as the perspectives in the development of literary theory in Bulgaria and, in general, the future of literary poetics and stylistics in the world of new media and changed receptive and creative realities.